Desnudando a masculinidade: representações de nudez e seminudez na estatuária funerária paulistana (1920-1950) - Carneiro, Maristela (2016)
This thesis investigates the use of nudity and seminudity and the multiple representations of masculinity in the modern funerary art at the city of São Paulo, looking at the collection of sculptures of the Consolação, Araçá and São Paulo cemeteries, situated in São Paulo State Capital, between 1920 and 1950. This work is a result of the doctorate research done for in the post-graduation program in History, at Universidade Federal de Goiás PPGH/UFG, supervised by Professor Dr. Maria Elizia Borges, furthermore by other resources obtained during the Sandwich Doctorate at Facoltà di Architettura dell'Università degli Studi di Napoli “Federico II”, under supervision of Professor Dr. Fábio Mangone. It is questioned which social and cultural aspects symbolize such male images, paying attention to the proper functions of the space of the cemetery, as an architectural object by definition. These are seen through the prism of Art History, allowing the terms – Art and History – to criticize and transform each other, opening disciplinary borders, as well as conceptual and linguistic ones, enabling for the domain of the historian to be modified by interventions of Art. Through the tabulation of male image occurrences, partially or completely naked, is observed that Italian aesthetic premises, especially those of the Novecento, have significant influence over the elaboration of São Paulo funerary art. This sculptures utilize often depictions that highlight sensibility in face of death, as well as the virility associated with work, on the other hand – in other words, there is no single, unchanging discourse on masculinity in the time period investigated. The analysis of the composition of the sculptures allow reconstructing partially the musings of the sculptors and their aesthetic expressivity as well as the meanings of their use of nudity and seminudity in the funerary art of the period. Furthermore, it is poited out that open air cemeteries allow for the exhibition of depictions of a masculinity sensitive and/or virile with greater expressive liberty. In short, these sculptures, as images, are historically localized and at the same time, bearers of a variety of temporalities and spatialities in the foundations, ever permeated by a continuous process of reconfiguration, from both, Past and Present. “Baring” them allows to find vestiges of Italian expression in the Tropical lands.